Violence Against Children (Child Abuse) in an Islamic Legal Perspective - Rahmadani, Putra; Hardani, Sofia; Wahidin, Wahidin (AL-FIKRA, 2024)
Violence against children is a serious problem that occurs in Indonesia. In Islam, violence against children is strictly prohibited and is considered an act that harms children and violates their rights. The aim of this research is to find out how Islamic law is applied in handling cases of violence against children (Child Abuse) in Indonesia. The method used in this research is literature study, by collecting data from primary and secondary sources related to this topic. The research results show that the application of Islamic law in handling cases of violence against children in Indonesia is not optimal. Several factors such as the community's lack of knowledge about Islamic law, lack of support from the authorities, and lack of skilled human resources in handling cases of violence against children are obstacles to the application of Islamic law in handling these cases. Therefore, efforts are needed to increase public understanding of Islamic law and strengthen cooperation between the authorities and the community in handling cases of violence against children. It is hoped that this research can make a positive contribution to efforts to handle cases of violence against children in Indonesia through a more optimal application of Islamic law.Keywords: Children, Violence, Education, Islamic Law